Studien zum Dual Eine Darstellung am niedersorbischen Neuen Testament des Miklawuš Jakubica (1548). Eine sprachwissenschaftliche Analyse - Unger, Mike (Specimina philologiae Slavicae, 1998)
The aim of this study is to describe and analyze the dual system of the New Testament of Miklavuš Jakubica (1548), because of the Du. a variety of individual studies exist, such. For example, to discuss the numerus category in Slavic in general, general representations of Sorbian with descriptions of dual paradigms, descriptions of individual inflectional paradigms of Ns, their peculiarities and genesis (...). The author sets himself the goal, after some introductory remarks on the translation of the NT by Miklawuš Jakubica in the second chapter, to discuss theoretical foundations of the morphological category, essentially referring to the number in general, the origin of the Du. and its different forms, like natural or free, you. with two and both and anaphoric you. will be received. The investigation is done both from a synchronous and a diachronic point of view, since paradigmatic comparisons with older ns. Grammars as well as with the contemporary language to be drawn.